EFEK IMUNOMODULATOR DARI KOMBINASI EKSTRAK ETANOL HERBA SAMBILOTO (Andrographis paniculata (Burm. f.) Nees) DAN RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb.) TERHADAP PROLIFERASI SEL LIMFOSIT MENCIT Balb/c SECARA IN VITRO - Damriati Azimah; Yuswanto Yuswanto; Wahyono Wahyono (Majalah Obat Tradisional, 2016)
Our susceptibility to various infectious diseases can be avoided by increasing the specific immune responses either by the proliferation of lymphocytes. Immunomodulator effect of Andrographis paniculata (Burm.f.) Nees) and Curcuma xanthorrhiza Roxb have been well evaluated. Empirically, the East Borneo’s tribe combined both herbs to treat jaundice disease. However, scientific evidence is still needed in their use as a drug candidate. This study explores further effect of the immunomodulator from 5 ethanol extract groups. Quantitative analysis was also completed using a densitometer to obtain andrographolide and curcumin levels of ethanol extract. Lymphocyte proliferation was tested by using MTT colorimetric method, the results was read by an ELISA reader and statistically analyzed with One-Way ANOVA test with 95 % of confidence level. The maceration yield of sambiloto ethanol extract (EES) and temulawak ethanol extract (EET) were respectively 5.78 % w / w and 3.92 % w / w. The results of quantitative analysis in 28.6 mg EES contained 11.43 % andrographolide and from the 251.8 mg EET contained 28.79 % curcumin. From the MTT test, all treatment groups were significantly different from the control group. Based on the OD values, the best combination to increase lymphocyte cell proliferation ETS was a group contained 56.25 mg of temulawak and 18.75 mg of sambiloto in 1 ml of solvent. Nonetheless, the value was not higher than the ability of ET in increasing cell proliferation.